2016
DOI: 10.1044/2015_jslhr-s-15-0086
|View full text |Cite
|
Sign up to set email alerts
|

Dysarthria in Adults With Cerebral Palsy: Clinical Presentation and Impacts on Communication

Abstract: This study provides an overview on the clinical presentation of dysarthria in a convenience sample of adults with CP. The complexity of the functional impairment described and the consequences on the individuals' communication call for a stronger consideration of dysarthria in CP both in clinical care and in research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 60 publications
2
37
0
1
Order By: Relevance
“…The question of what (combination of ) factors explain the change in intelligibility observed therefore remains. Lee et al (2014) and Schölderle et al (2016) have demonstrated the impact of articulatory precision on intelligibility for children and adults who have dysarthria and cerebral palsy. The potential effect of the therapy on articulatory skill and ability to produce easily perceived speech contrasts therefore warrants further attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of what (combination of ) factors explain the change in intelligibility observed therefore remains. Lee et al (2014) and Schölderle et al (2016) have demonstrated the impact of articulatory precision on intelligibility for children and adults who have dysarthria and cerebral palsy. The potential effect of the therapy on articulatory skill and ability to produce easily perceived speech contrasts therefore warrants further attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, acoustic analysis suggest that phonetic contrasts such as fricative-affricate and voice-voiceless contrasts may be marked but not perceived by listeners (Ansel and Kent 1992), possibly because of the weak aero-acoustic signal. Recent research suggests that articulatory, respiratory and prosodic impairment are most strongly associated with intelligibility for children and adults with cerebral palsy who have dysarthria , Schölderle et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, slowed speaking rate tends to be a characteristic of dysarthria post-stroke (Mackenzie, 2011), which may not significantly impact intelligibility (Blanchet & Snyder, 2010) and, therefore, may not be targeted or prioritized in management. Conversely, Schölderle, Staiger, Lampe, Strecker and Ziegler (2016) reported respiration and phonation as subsystems most prominently affected in CP; however, given that only 10 respondents had patients with CP on their current caseload, management practices for CP are unlikely to be overtly reflected in the survey results. The use of instrumentation was noted to be limited, consistent with Conway and Walshe (2015).…”
Section: Discussionmentioning
confidence: 92%
“…The speech presentations of children with dysarthria secondary to CP are diverse, some presenting with only a mild dysarthria and others presenting with anarthria, resulting in no functional verbal communication (Hustad, Gorton, & Lee, 2010). Even speakers with CP who have similar intelligibility levels can have widely varying perceptual and acoustic speech features (Allison & Hustad, 2018;Schölderle, Staiger, Lampe, Strecker, & Ziegler, 2016). Despite this heterogeneity, variations in profiles of abnormal speech features have not been well characterized in children with CP.…”
mentioning
confidence: 99%